Impact of caffeine and vitamin D3 on the body-weight of pregnant BALB/c mice - Khan, Maimoona; Abdullah, Muhammad Saad; Mushtaq, Fareeha; Umbreen, Faiza; Kiani, Muhammad Rizwan Bashir; Shahid, Ayesha (Journal of Rawalpindi Medical College, 2023)
Objective: To investigate the effect of caffeine and Vitamin D3 on the body weight of pregnant BALB/c mice. Design of Study: An RCT (Randomized control trial) in the Lab. Place and Duration of Study: The study was carried out at Anatomy Department, Army Medical College (AMC), Rawalpindi, in collaboration with National Institute of Health (NIH), Islamabad, from Oct 2018 to Oct 2019. Material and Methods: Six-week old pregnant BALB/c mice, thirty (30) in number, weighing 26-28g, were taken and divided into three groups with 10 pregnant mice in each group. The control group G1 was given standard diet with water ad libitum for 21 days. The animals in experimental group G2, in addition to the standard diet, were given 10mg of caffeine per 100g body-weight once a day on alternate days by oral gavage for 21 days. Similarly, mice in group G3, in addition to the diet of group G2, were given 0.1µg of vitamin D3 per day by oral gavage for 21 days. The body-weights on 1st day, 7th day, 14th day and 21st day of gestation in all the groups were measured to determine the influence of caffeine and vitamin D3. Results: Mean body-weights of mice in control group G1 were noted as 26.8 ± 0.789g, 30.7 ± 0.949g, 36 ± 0.667g and 42 ± 1.054g on 1st, 7th, 14th and 21st day of gestation, respectively. The mean body-weights of experimental group G2 were recorded to be 26.7 ± 0.675g, 29.9 ± 0.738g, 34.3 ± 0.823g and 39.5 ± 0.972g on 1st, 7th, 14th and 21th day of gestation, respectively. The mean body-weights of experimental group G3 were determined as 26.8 ± 0.632g, 30.4 ± 0.699g, 34.6 ± 0.516g and 40.5 ± 0.850g on 1st, 7th, 14th and 21st day of gestation, respectively. In comparison to the control group G1, the body-weights of animals in experimental group G2 showed more decrease in accrual of body-weight than noted in experimental group G3. Conclusion: Caffeine intake has decreasing influence on the growth of body-weight in pregnant mice while intake of vitamin D3 somewhat nullifies the harmful effect of caffeine on body-weight.